The impact of Malaysian public sector in the relationship between transformational leadership styles and career development - Ahmad, Rohana; Saad, Mazni (Taylor & Francis Group, 2019)
A systematic succession planning program, couple with solid career development is important to public sector employees. With this in mind, practicing the appropriate leadership strategy may contribute to a good management system. Therefore, this study intends to explore the relationship between leadership styles and career development program. The questionnaires also probed subordinates perceptions of leadership styles and expectations for greater career development. Quantitative research design was employed by distributing survey questionnaires to 576 Malaysian Public Sector government servants. The results of this research offer new insights into the importance of leadership values in the succession planning of government organizations.